New taxa, new records and redefined concepts in the Elaphoglossum sect. Elaphoglossum subsec. Pachyglossa (Lomariopsidaceae) from Mexico and Central America - Rojas-Alvarado, Alexander Fco (Universidad de Costa Rica, 2003)
Doce especies son descritas en el taxonómicamente difícil complejo Elaphoglossum latifolium (Sw.) J. Sm. (sect. Elaphoglossum): Elaphoglossum angustifrons A. Rojas, E. delgadilloanum A. Rojas, E. ellipticifolium A. Rojas, E. incognitum A. Rojas, E. mesoamericanum A. Rojas, E. nicaraguense A. Rojas, E. polypodium A. Rojas, E. tejeroanum A. Rojas, E. reptans A. Rojas, E. terrestre A. Rojas, E. variabile A. Rojas y E. zavale A. Rojas. También E. latifolium (Sw.) J. Sm. y E. sartorii (Liebm.) Mickel son corregidos, E. andicola (Fée) T. Moore y E. sporadolepis (Kunze ex Kuhn) T. Moore son informadas